2011
DOI: 10.15241/raw.1.1.71
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Professional Counselors: Survey of College Student Views

Abstract: Numerous sources of information influence how individuals perceive professional counselors. The stressors associated with entering college, developmental differences, and factors associated with service fees may further impact how college students view mental health professionals and may ultimately influence when, for what issues, and with whom they seek support. Individual perceptions of professional counselors furthermore impress upon the overall identity of the counseling profession. Two hundred and sixty-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Results regarding students' perceptions of marriage and family therapists, psychologists, social workers, and professional counselors have been presented elsewhere. [9][10][11][12][13][14][15] …”
Section: Methodsmentioning
confidence: 99%
“…Results regarding students' perceptions of marriage and family therapists, psychologists, social workers, and professional counselors have been presented elsewhere. [9][10][11][12][13][14][15] …”
Section: Methodsmentioning
confidence: 99%
“…However, due to space constraints, in this present journal article we will only examine the reported student perceptions regarding psychiatric nurses. Elsewhere (Firmin, Wantz, Firmin, & Wantz, 2012;Tse & Firmin, 2010;Wantz & Firmin, 2011) results were reported regarding the students' perceptions for marriage and family therapists, professional counselors, psychologists, and school counselors.…”
Section: Methodsmentioning
confidence: 99%
“…6 Researchers further reported that students also felt uncomfortable at the idea of counseling as well as the limitations of confidentiality that it would present, especially when students do not consider professionals to be competent. 12,14 Men tend to have more negative attitudes toward seeking help from counseling services than women. 9 Finally, some of the barriers surrounding counseling services and their continual lack of use include negative stigmas and a lack of understanding of psychological disorders as well as what services are offered.…”
Section: Introductionmentioning
confidence: 99%